2020
DOI: 10.1093/jbcr/iraa035
|View full text |Cite
|
Sign up to set email alerts
|

Closure of Persistent Tracheocutaneous Fistulas in Pediatric Burn Patients*

Abstract: Abstract Tracheocutaneous fistula (TCF) is a common complication that occurs after decannulation of a long-term tracheostomy. Numerous studies have demonstrated the incidence of TCF formation to positively correlate with an increasing duration of cannulation, specifically in children. Treatment of a persistent TCF in a child has been well described in the literature, with good response to local measures such as curettage and silver nitrate. When this fails, fistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…20 In fact, studies of pediatric burn patients have suggested that poor wound healing and delayed re-epithelialization can increase the risk for persistent TCF after decannulation. 21 Tissue scarring above the stoma from open airway surgery dissection might limit contracture of the stoma site and explain the high rate of persistent TCF. Extending the inferior limit of soft tissue dissection to the undersurface of the tracheostomy stoma is routine.…”
Section: Discussionmentioning
confidence: 99%
“…20 In fact, studies of pediatric burn patients have suggested that poor wound healing and delayed re-epithelialization can increase the risk for persistent TCF after decannulation. 21 Tissue scarring above the stoma from open airway surgery dissection might limit contracture of the stoma site and explain the high rate of persistent TCF. Extending the inferior limit of soft tissue dissection to the undersurface of the tracheostomy stoma is routine.…”
Section: Discussionmentioning
confidence: 99%
“…In some situations, reintubation, reinsertion of tracheostomy, or insertion of a tracheal stent has been utilised 6 . Cases of other conservative strategies aimed at obliterating the fistulous tract and promoting wound healing have been reported, including local curettage, electrocautery, or the use of silver nitrate 4 …”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the positive pressure associated with these therapies contributed to splinting of the stomal tract and precluded the apposition required for wound healing. Persistent air leak from the TCF resulted in poor sleep quality and tolerability of NIPPV and is postulated to have resulted in decruitment of basal lung segments, creating an environment conducive to impaired sputum clearance and recurrent LRTI 1–4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations